A Crisis in “Open Access”: Should Communication Scholarly Outputs Take 77 Years to Become Open Access? - Ghanbari Baghestan, Abbas; Khaniki, Hadi; Kalantari, Abdolhosein; Akhtari-Zavare, Mehrnoosh; Farahmand, Elaheh; Tamam, Ezhar; Ale Ebrahim, Nader; Sabani, Havva; Danaee, Mahmoud (SAGE Publications, 2019)
This study diachronically investigates the trend of the “open access” in the Web of Science (WoS) category of “communication.” To evaluate the trend, data were collected from 184 categories of WoS from 1980 to 2017. A total of 87,997,893 documents were obtained, of which 95,304 (0.10%) were in the category of “communication.” In average, 4.24% of the documents in all 184 categories were open access. While in communication, it was 3.29%, which ranked communication 116 out of 184. An Open Access Index (OAI) was developed to predict the trend of open access in communication. Based on the OAI, communication needs 77 years to fully reach open access, which undeniably can be considered as “crisis in scientific publishing” in this field. Given this stunning information, it is the time for a global call for “open access” by communication scholars across the world. Future research should investigate whether the current business models of publications in communication scholarships are encouraging open access or pose unnecessary restrictions on knowledge development.